The Influence of Organizational Culture, Job Satisfaction, and Information Asymmetry on the Tendency Toward Fraud at PT. Artha Gita Medan - Muhammad Abyas Haqqi; T. Lyza Tahura Chairunnisa (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to analyze the influence of organizational culture, job satisfaction, and information asymmetry on the tendency toward fraud. The population in this study consisted of 105 employees, and the sample was determined using a saturated sampling technique, in which all members of the population were included as research samples. The analytical method used in this study was multiple linear regression analysis. The results of the study indicate that organizational culture has a positive and significant effect on the tendency toward fraud. Job satisfaction also has a positive and significant effect on the tendency toward fraud. Likewise, information asymmetry has a positive and significant effect on the tendency toward fraud. Simultaneously, the findings show that organizational culture, job satisfaction, and information asymmetry significantly influence the tendency toward fraud at PT. Artha Gita Medan.